रोहतास गढ़ - रूइदास गढ़ और उराँव - कुँडुख़र - (:unkn) unknown (Jharkhand Jharokha Ranchi, 2017)
रोहतास गढ़ - रूइदास गढ़ और उराँव - कुँडुख़र provides an historical overview of the Kurukh community.
Rohtasgarh - Ruidasgarh Aur Oron - Kurukhar
Keywords: Kurukh; रोहतास गढ़; रूइदास गढ़; उराँव; कुँडुख़र; Rohtasgarh; Ruidasgarh; Oron; Kurukhar; Bharatavani; Knowledge Through Indian Languages; History; Hindi